PENGELOLAAN WAKAF TUNAI UNTUK PEMBERDAYAAN UMKM DI KOPERASI MASJID SABILILLAH KOTA MALANG - Abdurrasyid, Muhammad Faiq; Athoillah, Moh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to see how the management of cash waqf conducted by sabilillah mosque cooperatives in Malang city which will be used for the empowerment of MSMEs around the Sabilillah Mosque Cooperative in Malang City.This study uses descriptive qualitative methods where researchers plunge directly into the field to see and ask directly to trusted sources.And in the result of cash waqf managed by Sabilillah Mosque Cooperative, Malang City has been running quite well and also has a positive impact on MSMEs who receive capital assistance funds from cash waqf managed by Sabilillah Mosque Cooperative in Malang City.